The Legal Implications of AI in Corporate Governance From Directors’ Responsibilities to Regulatory Evolution - Pastirk, Gal; Primec, Andreja (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
Integrating artificial intelligence (AI) into corporate governance presents a dual challenge. On one hand, it offers significant opportunities for enhanced efficiency and strategic decision-making. On the other hand, it introduces complex legal, ethical, and financial challenges, particularly concerning directors' fiduciary duties. As AI transforms business processes, corporate leaders must ensure compliance, transparency, and accountability, particularly about shareholders, investors, and business partners. A significant element of AI governance is the regulatory leadership demonstrated by the European Union, with the AI Act providing the first comprehensive legal framework for AI adoption. In an era of political uncertainty, stakeholders strive to balance fostering AI-driven innovation and maintaining accountability. Directors must align corporate governance structures with these regulations to ensure AI's legal and ethical use. Financial reporting has a pivotal role in disclosing AI-related risks to investors and regulatory bodies, thereby strengthening corporate transparency and accountability. Corporate leadership is thus responsible for establishing effective oversight mechanisms that mitigate risks while promoting responsible AI-driven innovation. By enhancing governance structures and ensuring comprehensive AI supervision, directors will uphold corporate integrity, sustain investor confidence, and successfully navigate the evolving regulatory landscape.